Matsuda Denjuro’s service in Hakodate and the surrounding area from October 31, 1799, to January 1, 1801 (Based on the “Tales of the Northern Barbarians”) - A. V. Klimov (Японские исследования)
The manuscript “Tales of the Northern Barbarians” (“Hokuidan,” 北夷談) by Matsuda Denjūrō 松田伝十郎 (1769–1843) is a valuable source on the history of Russian-Japanese relations, the development of the northern territories inhabited by the Ainu conducted by the Japanese, relations between the Ainu and the Japanese, their barter trade. The written source consists of seven notebooks. The manuscript was created in the first years of the Bunsei era (文政, 1818–1831). It describes the events from 1799 to 1822 in chronological order, i.e., events that occurred during the 24 years of Matsuda's service in the lands of the Ainu. The manuscript is written in cursive (Japanese: "grass writing," sōsho 草書). The second half of the first book examines the bear festival and the inau, cult objects of the Ainu, which were described in detail by the author in [Klimov 2024].